Attractant potential of Enterobacter cloacae and its metabolites to Bactrocera dorsalis (Hendel) - Duan, Yawen; Li, Anjuan; Zhang, Lin; Yin, Chongwen; Li, Zhihong; Liu, Lijun (Frontiers in Physiology, 2024)
Objective Bactrocera dorsalis (Hendel) has a wide host range. It has been the most important quarantine pest in many countries or regions. Currently, chemical control and bait trapping are mainly used in the monitoring, prevention, and control of B. dorsalis. However, chemical control will cause pollution of the environment and drug resistance of insects. Methyl eugenol, the main attractant currently used, can only attract males of B. dorsalis. Methods This study focused on the attractant function and active substances of one key intestinal bacterium, Enterobacter cloacae, which was isolated from B. dorsalis. Results First, the attraction of the E. cloacae autoclaved supernatant to male and female adults of 0, 6, and 15 days post-emergence was confirmed using a Y-type olfactometer. Subsequently, through metabolome sequencing and bioassays, L-prolinamide was identified and confirmed as the most effective attractant for B. dorsalis. Finally, the synergistic effect of L-prolinamide with the sex attractant ME was validated through field experiments. This study confirmed the attraction effect of E. cloacae on B. dorsalis and also proved the attraction effect of L-prolinamide, the metabolite of E. cloacae, on B. dorsalis. This laid a theoretical foundation for the development of a new attractant and safe, green, and efficient prevention and control technology of B. dorsalis.